Hegelian Practical Freedom and Nature - Nicolás García Mills (Journal of Modern Philosophy)
In this paper, I argue that, despite his remarks to the effect that freedom consists in the ‘movement’ away from nature, Hegel conceives of the will as a natural power or capacity of sorts. I articulate and defend this thesis in two steps. In section I of the paper, I sketch a reading of Hegel’s account of practical freedom in the Introduction to the Philosophy of Right as a capacity to respond to ethical requirements or duties. In section II, I argue that the will, on that account, qualifies for Hegel as natural in the following two respects: First, in the good or virtuous case, our responsiveness to ethical requirements exhibits features similar to the lawlike behavior of subhuman denizens of the natural world and other law-governed natural processes. Second, our capacity for practical freedom emerges through processes of habituation from the exercises of capacities that we share with other animals. Although the second thesis is the more important of the two for the purposes of naturalizing Hegel’s account of the will, I believe it has not yet been the focus of satisfactory scholarly attention. I thus hope to help remedy what I take to be a gap in the recent literature.